Enhancing the effectiveness of digital transformation on teaching in higher education in Kuwait - Alkandari, Fouad; Alsaber, Ahmad; Al-Kandari, Anwaar; Alboloushi, Bedour; AlMutairi, Shihanah (Frontiers in Education, 2024)
Introduction This study investigates the digital citizenship behavior (DCB) and behavioral intention (BI) of faculty members at the Public Authority for Applied Education and Training (PAAET) colleges in Kuwait. The research aims to evaluate the effectiveness of technology in teaching and provide a case study of higher educational institutions in Kuwait. The study’s theoretical framework focuses on four key factors: performance expectancy (PE), effort expectancy (EE), social influence (SI), and facilitating conditions (FC), examining their impact on faculty readiness (RED) through the mediation of both BI and DCB. A total of 28 hypotheses were tested, exploring direct and indirect relationships among these variables. Methods A survey was conducted among 122 faculty members from PAAET colleges in Kuwait. The questionnaire measured the participants’ perceptions of PE, EE, SI, and FC, along with their BI and DCB. The study employed statistical methods to analyze the data and test the 28 hypotheses, aiming to identify significant paths of relationships that contribute to faculty readiness for technology use in education. Results The findings confirmed eight significant paths of relationships, highlighting the importance of inputs such as effort and social influence and their impact on performance as an output in determining faculty readiness. However, the study raised empirical doubts about the remaining 20 hypotheses, providing new evidence that challenges the currently established relationships between technology acceptance and digital citizenship. Discussion The study offers valuable insights into the factors influencing the effective use of technology in higher education institutions in Kuwait. It suggests that while some pathways, such as effort and social influence, significantly contribute to faculty readiness, other expected relationships may not hold as previously thought. This new evidence calls for a reevaluation of the existing models of technology acceptance and digital citizenship. The results have important implications for policy and practice, offering guidance on enhancing technology use among faculty members in educational settings. The study contributes to the broader discussion on digital transformation in education, providing a comprehensive understanding of the key factors that affect faculty readiness for adopting new technologies.